MODEL PEMBELAJARAN EKONOMI SYARI’AH MELALUI CTL PADA JURUSAN PENDIDIKAN EKONOMI UNIVERSITAS NEGERI SURABAYA - Yoyok Soesatyo (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2014)
The Purpose of this research is to describe the concept of syari’ah economics as a comprehensive learning model for student in Surabaya state university majoring in to be economics education, to be able to describe, connect with reality or phenomena and interpret the solutions of the phenomenon that exist in the community based on syari’ah economy. The method that used in this research is descriptive research method that describes the result of the research which obtained from the respondents and field observations both from primary and secondary data. The finding in this research indicate that understanding of the Islamic economismaterial given by using direct instructional model is still less than the standard of competencespecified, therefore it is necessary efforts to increase the understanding material through appropriate learning model in this study is a CTL (Contectual Teaching Learning)